Dampak Pengembangan Auto Gate System terhadap Kelancaran In Out Truck pada Terminal Jamrud Utara Pelabuhan Tanjung Perak Surabaya - Garry Laksmana; Rizqi Aini Rakhman; Edi Kurniawan (Jurnal Bintang Pendidikan Indonesia, 2024)
The increasing era of globalization encourages sea transportation to continue to develop, one of its activities is loading and unloading. In loading and unloading activities, an obstacle that often occurs during the activity is the buildup/jam of trucks at the truck in and out gate of a port. At North Jamrud Port there will be a buildup of trucks in 2022 and then there will be development of the Auto Gate System in 2023. This research aims to find out how significant the impact of the development of the Auto Gate System is on the smooth operation of the port (in and out of trucks) in 2023. The research method used in this research is quantitative. One Group Pretest Posttest. This research data uses primary data and secondary data obtained from the company PT. Pelindo Multi Terminal Jamrud branch. Data collection techniques include field observation and literature study. The results obtained are that truck queues at the port gate can be reduced significantly, reducing congestion and smoothing traffic flow in the port area.